90 Anaesthetic and peri-operative complications in paediatric patients with brugada syndrome. (22nd November 2019) - Gan, Jo Han; Sri, Anita; Kaski, Juan; Hepburn, Lucy; Starling, Luke
Abstract : Background: Brugada syndrome (BrS) is a cardiac ion channelopathy, typically affecting autosomal-dominantly inherited mutations in the SCN5A gene. BrS predisposes to potentially malignant arrhythmias and sudden cardiac death. Routinely administered anaesthetic drugs may trigger malignant arrhythmias in susceptible individuals. This is the first review of drugs used during anaesthetic management of children either diagnosed with or at risk BrS, to determine if such agents pose a risk of perioperative arrhythmia. Patients: Thirty-five patients were identified from our BrS database who had at least one anaesthetic encounter. Twenty-one had a confirmed diagnosis of BrS (B group) while fourteen were classified as at-risk (A group). They underwent 66 anaesthetic interventions (B=29, A=37). Females comprised 45.7% while median age was 8.3years (IQR 5.3–12.8) and median weight was 29.5 kg (IQR 20.4–40). Method: Anaesthetic and recovery records were retrospectively reviewed. Drugs used were compared with those recommended to be avoided or preferably avoided on brugadadrugs.org website. Hemodynamic and cardiac complications during anaesthesia were assessed for possible association with these drugs. Results: From the list of drugs recommended to avoid in BrS, the following were used: propofol (B=15, A=20) and local anaesthetics agents (B=18, A=13). Haemodynamic problems were encountered in 4 cases. One case required use of vasoconstrictor due to hypotension, the remainder resolved spontaneously. None were attributed to adverse effects of anaesthetic drugs in the context of BrS. There were no documented arrhythmias. Conclusions: Although no significant adverse reactions to anaesthetic drugs were observed, there remains a theoretical risk of arrhythmia induced by certain agents in predisposed individuals with BrS. We recommend children diagnosed with or at risk of BrS be anaesthetised in a tertiary paediatric centre following advanced planning with paediatric cardiologists experienced in the management of inherited arrhythmias. Continuous cardiac monitoring is mandatory, whilst resuscitation equipment and expertise should be immediately available.